Bank Indonesia dalam Tata Pemerintahan Indonesia - Maqdir Ismail (Jurnal Hukum IUS QUIA IUSTUM, 2010)
This research focuses on problems as follows: First, position and role of Bank Indonesia as a state body in Indonesia; Second, independency of central bank in performing its monetary function. This research is a juridical normative research using primary legal source which is legislation concerning central bank. Data is collected through document study and literary study. This research concludes that position of Bank Indonesia as a legal entity should have been included in the explanation of constitution system. Legislation should emphasize that Bank Indonesia is a central bank not a state body. Central Bank should have independency to avoid conflict of interest.Key words : Central bank, governance , independency